Purification of corosolic acid from Lagestroema speciosa (Banaba) leaves using centrifugal thin layer chromatography - Pilarco, Angel Grace (2016.)
Diabetes is a chronic, metabolic disease characterized by high levels of blood glucose which leads to serious damage to the blood vessels, eyes, heart and kidneys (WHO. 2016). Currently, there is no known cure for diabetes. However, the use of Lagestroema speciosa (banaba) leaves in the treatment of the disease is gaining popularity due to its ability to lower blood glucose levels (Klein et al., 2007). Corosolic acid is the compound responsible for L. speciosa?s antidiabetic property and is found in the leaves of the plant. The compound is usually extracted through reflux procedures before being analyzed using HPLC. Centrifugal thin layer chromatography is a chromatographic technique usually well-known as a preparative prepurification technique before samples are subjected to further analyses. This study is the first to use centrifugal thin layer chromatography in the purification of corosolic acid from the leaves of L. speciosa while using three sequential extractions. Upon HPLC analysis, the amount of corosolic acid obtained was around 2.76 x 10-7 g. Compared to the 0.31-0.38 mg amount of corosolic acid extracted using a different method (Vijaykumar, 2006), the amount obtained in this study is very low leading to an optimization on the solvent system used in this study and the possibility of using another extraction method.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Banana leaves, Lagestroema speciosa; Chromatography; CTLC; Corolosic acid; Diabetes